Deceiving Someone into Having Sex - Theron, Shirah (The Stellenbosch Socratic Journal, 2023)
This paper aims to provide an in-depth examination of the fundamental elements of rape, specifically focusing on intention and consent, within the context of “deceiving someone into having sex”. The analysis will involve exploring model cases and scrutinising the intentions of both the deceiver and the deceived in relation to consent. Through conceptual analysis, the concept of “deceiving someone into having sex” will be clarified, drawing insights from typical applications of this concept. Additionally, this paper will critically evaluate the main arguments against these conceptualisations of “deceiving someone into having sex”. This is done to demonstrate the flaws that undermine these arguments, thus highlighting the insufficiency of these approaches in fully discrediting the concept. Moreover, it will be argued that deceiving someone into having sex can be regarded as a form of coercion, and thus rape, aligning with the established criteria for identifying rape cases. In conclusion, this paper argues that the conception of “deceiving someone into having sex” as a form of rape challenges the narrow framework through which we traditionally understand rape, necessitating the recognition that the scope of the concept of rape extends beyond our previous limits.